Students’ Perception on Synchronous and Asynchronous Learning at Indonesian English Translation of English Education Department at Universitas Negeri Padang - Zahara Azura; Carbiriena Solusia (Journal of English Language Teaching, 2022)
Synchronous and asynchronous learning are type of online learning mode that commonly used in online learning. The purpose of this research was to find outs students’ perception on synchronous and asynchronous learning during classroom discussion at Indonesian English Translation class of English Education Department at Universitas Negeri Padang. The sixth semester students taking Indonesian English Translation class of English Education Department at Universitas Negeri Padang in academic year of 2021/2022 was as the population of this research. There were 40 students who were selected as the sample using total sampling. This research used a descriptive research design. A closed-ended questionnaire was used to gain the data for this research. Based on the findings and discussion, it was indicated that almost all of the students had positive perception on the advantages of synchronous learning and asynchronous learning at Indonesian English Translation class during classroom discussion. It was also found that the students were more active to participate in a discussion forum on e-learning because they felt more confident about sharing ideas using text rather than speaking directly.